2007
DOI: 10.2135/cropsci2006.05.0335
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Spectral Characteristics of Rice Canopy Infested with Brown Planthopper and Leaffolder

Abstract: Potted experiments of rice (Oryza sativa L.) plants were conducted to produce various scales of brown planthopper [Nilaparvata lugens (Stål), Homoptera:Delphacidae] and leaffolder [Cnaphalocrosis medinalis Guenee (Lep., Pyralidae)] infestations, respectively, for canopy hyperspectral reflectance measurements, and then to identify spectral characteristics (SCs) associated with insect infestations leading to the establishment of spectral models for severity assessment. By linear correlation intensity analysis, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 25 publications
6
76
0
Order By: Relevance
“…Mohammad et al showed that the visible and infrared regions of the electromagnetic spectra provide the maximum information on physiological stress levels in an affected plant [14]. Some of the wavelengths specific to a disease can be used to detect plant disease [15].Optimum spectral ranges have been suggested to detect different disease; 425, 685 and 735 nm to detect citrus canker [16], 737-925 nm to detect brown plant hopper disease of rice [17], 426 nm for brown plant hopper and leaf folder infestation of rice [18], and 800 to 1100 nm to identify leaf miner damage of tomato [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mohammad et al showed that the visible and infrared regions of the electromagnetic spectra provide the maximum information on physiological stress levels in an affected plant [14]. Some of the wavelengths specific to a disease can be used to detect plant disease [15].Optimum spectral ranges have been suggested to detect different disease; 425, 685 and 735 nm to detect citrus canker [16], 737-925 nm to detect brown plant hopper disease of rice [17], 426 nm for brown plant hopper and leaf folder infestation of rice [18], and 800 to 1100 nm to identify leaf miner damage of tomato [19].…”
Section: Introductionmentioning
confidence: 99%
“…Reflectances of agriculture crops in the visible and infrared regions have been studied in order to estimate different crop properties and to assess growth status of the crop (Carter and Knapp 2001;Kumar et al 2001;Yang and Chen 2004;Yang et al 2007). Most healthy crop canopies generally have large reflectances in the near-infrared region (700-1300 nm; NIR) and smaller reflectances in the photosynthetically active region (400-700 nm; PAR) depending on photosynthetic activity (Hall et al 2002;Yang and Chen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, without knowledge of the frequencies and spatial extent of such losses, such information is of little value. Recent research has attempted to improve the situation by developing technologies to better detect pests including using remote sensing applications (Lamb and Brown, 2001;Yang et al, 2007). It will be necessary to continually update damage thresholds and estimated yield losses as climates and crop management practices change and because different rice varieties often have specific responses to pest attack (see Section 11).…”
Section: Pest Management For Rice: Scientific Approachesmentioning
confidence: 99%